Pembinaan Generasi Tangguh melalui Penguatan Karakter, Kepemimpinan, dan Patriotisme pada Mahasiswa Organisasi Kemahasiswaan Fakultas Ilmu Sosial dan Politik Universitas 17 Agustus 1945 Surabaya. - Sumiati Sumiati; Yahya Hajar Nur Faizin (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aimed to strengthen the character, leadership, and patriotism of student organization members at the Faculty of Social and Political Sciences, University of August 17, 1945 Surabaya. The program was initiated due to the lack of integration of values development, leadership, and social awareness within student organizational activities. The activity involved 130 students from various study programs representing the Student Representative Council, Student Executive Board, and student associations. The implementation method used a participatory training approach combined with mentoring through four stages: needs identification, character strengthening training, applied leadership training, and social problem mapping followed by action planning. The results indicated improved participants’ understanding of integrity, responsibility, empathy, and discipline, as well as enhanced communication, collaboration, and decision-making skills. This activity is important because it supports the development of resilient, value-oriented, and socially responsible students.